Sleep duration, health status, and subjective well-being: a population-based study - Margareth Guimarães Lima; Marilisa Berti de Azevedo Barros; Maria Filomena Ceolim; Edilson Zancanella; Tânia Aparecida Marchiori de Oliveira Cardoso (Universidade de São Paulo, 2018)
ABSTRACT OBJECTIVE To evaluate, in a population-based approach, the association of extreme sleep duration with sociodemographic factors, health, and well-being. METHODS We analyzed the data from the 2014/2015 Health Survey in the city of Campinas, State of São Paulo, Brazil (ISACamp), performed with 1,969 individuals (≥ 20 years old). Associations between the independent variable and short (≤ 6 hours) and long (≥ 9 hours) sleep were determined using the Rao-Scott chi-square test. The analyses were adjusted with multinomial logistic regression models. RESULTS Men, individuals aged 40 to 59, those with higher schooling, those who have one (OR = 1.47, 95%CI 1.02-2.12), two (OR = 1.73, 95%CI 1.07-2.80), or three or more (OR = 1.62, 95%CI 1.16-2.28) chronic diseases, and those with three or more health problems (OR = 1.96, 95%CI 1.22-3.17) were more likely to have a short sleep. The chance of long sleep was higher in widowers and lower in those who have more years of schooling, with higher income, worked, lived with more residents at home, and reported three or more diseases (OR = 0.68, 95%CI 0.48-0.97) and health problems. The chance of either short (OR = 2.41, 95%CI 1.51-3.87) or long sleep (OR = 2.07, 95%CI 1.23-3.48) was higher in unhappy individuals. CONCLUSIONS These findings highlight the higher chance of short sleep duration among men, among persons in productive age, and among those with a higher level of schooling in a Brazilian city. The association of short sleep with comorbidities and the association of happiness with extremes of sleep duration were also important results to understand the relation of sleep duration with health and well-being.